Investigasi Keterkaitan Adiksi Internet, Kepuasan Hidup dan Depresi: Investigating the Relationship between Internet Addiction, Life Satisfaction and Depression - Zaen, Fifin Nur; Aulia, Moch Agung; Aziz, Raisya; Auliya, Shefina; Saepullah, Willy; Fuji, Mita Deviani; Natanael, Yonathan (Psikologia : Jurnal Psikologi, 2024)
The problem of internet addiction is very important to be explored further with scientific studies. Considering more frequency the use of internet in the pandemic covid-19 era, especially for college students. The purpose of this study is to explore the relationship between internet addiction, life satisfaction, and depression in college students. Homogenous sampling was used to obtain the same criterion for 467 participants. The research design used is correlational research to determine the effect of one variable on other variables. Demographic analysis shows that students use the internet more in their daily lives to play games and access social media, compare to accessing study material and browsing information. Inferential analysis with regression found that there was no effect of internet addiction on life satisfaction and depression in college students. The finding of this study support previous studies, where online games and access to social media are the student’s favorite choices when accessing the internet, and this study which states that there is no correlation between the three variables are tested.